EFEKTIVITAS MODEL PEMBELAJARAN EDUTAINMENT DENGAN PENDEKATAN SAVIK TERHADAP PENINGKATAN MINAT DAN KEMANDIRIAN SISWA PADA MATERI TRIGONOMETRI KELAS X - Rahmawati, Alfiana; Prihaswati, Martyana; Purnomo, Eko Andy (Universitas Muhammadiyah Semarang, 2018)
Curriculum 2013 applied in SMA Institute of Indonesia Semarang demands that students learn independently, but in fact students used to be guided by teachers while studying, so students independence is weak. Student interest is still weak too, so it,s driving the low achievement of students of class X. The purpose of this study is to know whether the model of edutainment learning with SAVIK approach effectivel. This research is an experimental research, with population of all class X. The variables in this study consist of learning achievement, interest and independence. Methods of collecting data in the form of interviews,documentation, tests, questionnaires, and observations. The results showed that students achieve mastery with an average value of 79.54 and classical completeness of 82.14%. In addition, the influence test showed the influence of interest and independence of 68.9%. The result of average difference test shows that is experimental class is 79,54, and control class is 71,40. The result of improvement test in the experimental class is the increase of interest and independence, the increase is included in the medium level. The conclusion from this research is edutainment learning model with SAVIK approach to increasing interest and independence on the material of Trigonometry of class X is effective. Keywords: Edutainment, Independence, Interest,SAVIK.